From T‐Bills to Common Stocks: Investigating the Generality of Intra‐Week Return Seasonality - FLANNERY, MARK J.; PROTOPAPADAKIS, ARIS A. (Journal of Finance, 1988)
ABSTRACT The authors investigate the extent to which intra‐week seasonality still exists and whether its pattern is uniform across three stock indices and Treasury bonds with seven different maturities. They find that intra‐week seasonality continues to be significant and that its pattern is not uniform, either between the stock indices and the Treasury bonds or even among the bonds alone. A pattern shared by stocks and bonds is that Monday returns become increasingly negative with maturity. These findings suggest that neither institutional nor general‐equilibriumex planations by themselves can explain the pattern of intra‐week seasonality in securities markets.